2018
DOI: 10.1113/ep087035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of graviceptor stimulation initiated by off‐vertical axis rotation on ventilation

Abstract: It has been suggested that the otolith system is involved in the physiological response to changes in body orientation with respect to gravity. In studies on animals, an otolith-respiratory reflex has been observed, but data on humans are scarce and inconclusive, mainly because pure otolithic stimulation is difficult to produce in humans. To assess the otolithic-respiratory reflex in humans, we used an off-vertical axis rotation (OVAR) that produces periodic and pure stimulation of graviceptors. The inspirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, vestibular graviceptors predominate for vertical perception 32 while extra-vestibular graviceptors predominate for autonomic regulations 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, vestibular graviceptors predominate for vertical perception 32 while extra-vestibular graviceptors predominate for autonomic regulations 3 .…”
Section: Discussionmentioning
confidence: 99%
“…These sensors add to posture-related autonomic adaptations 3 and perception of vertical 32 . Several studies have been dedicated to deduce the proportional effect of vestibular and trunk graviceptors in some functions: it has been found that eye-movement is almost entirely controlled by the vestibular system 33 , while the autonomic functions and the perception of the vertical are affected by both gravity sensors 3,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that inputs from the trunk, including visceral graviceptors, can contribute to a sense of spatial orientation (21)(22)(23) and influence respiration (17). It has been demonstrated that after vestibular loss in humans somatosensory and proprioceptive signals take a bigger role in balance and postural control (18,28,43).…”
Section: Vestibulo-sympathetic Reflex In Bvl Patientsmentioning
confidence: 99%
“…A large amount of evidence from animal and human studies suggests that vestibular input participates in autonomic response to postural change through vestibulo-autonomic reflexes [1][2][3][4][5] . While it has been shown that the semicircular canals, the vestibular end organs specialized in detecting head rotations, may contribute to these vestibulo-autonomic reflexes, most studies have focused on the role of the otolith organs, the vestibular end organs specialized in detecting head linear acceleration (gravity and inertial acceleration).…”
mentioning
confidence: 99%